Investasi Cryptocurrency Berdasarkan Peraturan Bappebti No. 5 Tahun 2019 - Nitha, Dewa Ayu Fera; Westra, I Ketut (Jurnal Magister Hukum Udayana (Udayana Master Law Journal); Vol 9 No 4 (2020), 2020)
Current technological developments have digital money or cryptocurrency which is currently being used as an investment by the world community. Seeing this, the government has now issued CoFTRA Regulation Number 5 of 2019 concerning Technical Provisions for the Implementation of the Physical Asset Market in the Futures Exchange to ensure legal protection for investors and legal certainty in the event of a dispute. This study aims to analyze protection The law against Cryptocurrency Investors is reviewed based on Bappebti Regulation Number 5 of 2019 and analyzes the legal efforts made in the event of a dispute in cryptocurrency investment. The research method in this study uses normative legal research methods with a statutory approach and a conceptual approach. The results of this study show that the Indonesian Government has accommodated the interests of crypto asset trading as well as a guideline and clarity for the public regarding the government's recognition of the presence of bitcoin and virtual currancy, namely through Bappebti Number 5 of 2019 and dispute disputes that occur between cryptocurrency investors and cryptocurrency marketplaces by way of non-litigation and arbitration through the Commodity Futures Trading Arbitration Board (BAKTI). Perkembangan teknologi saat ini telah terdapat uang digital atau cryptocurrency yang saat ini dijadikan sebagai investasi oleh masyrakat dunia. Melihat hal tersebut kini pemerintah telah mengeluarkan Peraturan Bappebti Nomor 5 Tahun 2019 Tentang tentang Ketentuan Tekhnis Penyelenggaraan Pasar Fisik Asset Kripto (Crypto Asset) di Bursa Berjangka untuk memastikan adanya perlindungan hukum bagi para investor dan kepastian hukum apabila terdapat sengketa. Studi ini bertujuan untuk menganalisa perlindungan Hukum terhadap Para Investor Cryptocurrency dikaji berdasarkan Peraturan Bappebti Nomor 5 Tahun 2019 serta menganalisa upaya Hukum yang dilakukan apabila terjadi sengketa dalam investasi cryptocurrency. Metode penelitian dalam studi ini menggunakan metode penelitian hukum normatif dengan pendekatan perundang-undangan dan pendekatan konseptual. Hasil studi ini menunjukkan bahwa Pemerintah Indonesia telah mengakomodir kepentingan perdagangan kripto aset serta sebagai suatu pedoman dan kejelasan bagi masyarakat terkait pengakuan pemerintah terhadap kehadiran bitcoin dan virtual currancy yaitu melalui Bappebti Nomor 5 Tahun 2019 dan perselisihan sengketa yang terjadi antara investor cryptocurrency dengan marketplace cryptocurrency dapat diselesaikan dengan jalan non-litigasi dan abitrase melalui Badan Arbitrase Perdagangan Berjangka Komoditi (BAKTI).